Tracheal and cloacal bacterial diversity of red listed Eastern Imperial Eagle (Aquila heliaca) - Murtskhvaladze, Marine; Ninua, Levan; Budagashvili, Nika; Tevdoradze, Ekaterine; Gurgenidze, Zurab; Kotorashvili, Adam; Kotaria, Nato; Gavashelishvili, Alexander; Javakhishvili, Zurab (Frontiers in Microbiology, 2025)
This study aimed to improve knowledge of raptor microbiomes by providing the first description of tracheal and cloacal bacterial diversity of Eastern Imperial Eagles (Aquila heliaca). To date, only few studies are available and they are carried out mainly on captive birds. The Eastern Imperial Eagle is species of significant conservation concern and, therefore, characterization microbiota contributes valuable information to the field of avian microbiology and aids in conservation efforts for this threatened species, moreover, identification of avian and human pathogens within microbial communities and evaluation of potential threats to birds, humans, and other species are crucial for sustainably balancing the wellbeing of ecosystems, 3,500 OTUs were identified from each sample supported by ∼2.8 Million sequence reads. The tracheal and cloacal microbiomes were dominated by Gammaproteobacteria (67.5%), Bacilli (43.8%), and Negativicutes (22.0%). We detected dissimilarities between cloacal (unique 440 OTUs) and tracheal (337 unique OTUs) samples, and significant evidence of moderate positive monotonic relationship between cloacal and tracheal bacterial communities. No significant differences between individuals from different nests. Aquila heliaca can serve as an indicator of presence of bacterial species in its respective habitats. Efforts aiming at protection of red-listed birds may not presently prioritize microbiome considerations but integrating microbiome research into conservation strategies could yield significant benefits.